Sistem Pendukung Keputusan Pemilihan Motif Batik Solo Dengan Metode AHP - Grezian, Muhammad Savira, Fatah Yasin Al Irsyadi, S.T., M.T (2016)
Batik is a identity of Indonesia, especially in the city of Solo and now it needs to be batik the increasingly diverse existing motif batik Solo. This is the background to design and create web-based decision support system to facilitate the public in deciding which motif accordance with the wishes and needs , by using Analytical Hierarchy Process as a calculation algorithm for the design and implementation of the system . The results of the application of this system is emerging motif that corresponds to the input of age , price and type of fabric with reference to the weighting of each alternative and the criteria in AHP . So that once made these applications can help people, especially the solo city in terms of determining motif that suits your needs.